2017
DOI: 10.1007/s11523-017-0476-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting microRNAs As Cancer Therapeutics

Abstract: miRNAs are a well-studied class of non-coding RNAs, predominantly functioning to down-regulate gene expression from messenger RNA (mRNA) in a targeted manner by binding to complementary sequence on the target mRNA. Many miRNAs have been linked to the development of hallmarks of cancer. miRNAs represent valuable therapeutic targets to exploit in the search for novel cancer treatments, due to their ubiquitous expression and their ability to tightly regulate the gene expression of a whole host of genes and pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 168 publications
0
14
0
Order By: Relevance
“…There is strong evidence that miRNAs are tightly implicated in a mass of complex regulatory networks of crucial genes in a variety of tumors ( 52 - 54 ). It has been indicated that target genes of miRNAs are direct regulators of the hallmarks of cancer, including proliferation, cell cycle and cell apoptosis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence that miRNAs are tightly implicated in a mass of complex regulatory networks of crucial genes in a variety of tumors ( 52 - 54 ). It has been indicated that target genes of miRNAs are direct regulators of the hallmarks of cancer, including proliferation, cell cycle and cell apoptosis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that miRNAs are tightly implicated in a mass of complex regulatory networks of crucial genes in a variety of tumors ( 52 - 54 ). It has been indicated that target genes of miRNAs are direct regulators of the hallmarks of cancer, including proliferation, cell cycle and cell apoptosis ( 52 ). Tao et al found that a decreased miR-125a expression in osteosarcoma tissues, and its overexpression contributed to growth suppression in osteosarcoma cells by downregulating E2F2 expression ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that miRNA-based therapies may become a viable strategy for treating a broad range of disorders such as cancer and cardiovascular disease, among others (van Rooij and Kauppinen, 2014 ; Adams et al, 2017 ). Further, in oncology the aim is to downregulate or block the function of oncogenic miRNAs and/or upregulate expression of tumor suppressor miRNAs, for which different miRNA-targeting strategies have been proposed (as reviewed in Ling et al, 2013 ; Li and Rana, 2014 ; Robb et al, 2017 ). Replacement of tumor suppressor miRNAs typically involves the introduction of synthetic miRNA mimics or miRNA expression vectors.…”
Section: Overview Of Mirna Biogenesis and Functionmentioning
confidence: 99%
“…How this might be achieved requires a more nuanced understanding of the regulation of miR-155 expression in different cellular contexts. MicroRNA-based therapy offers significant promise that has seen multiple ongoing preclinical and early-phase human trials, although it should be pointed out that substantial hurdles remain regarding the safety of high/frequent dose regimes and targeted delivery strategies [71].…”
Section: Clinical Implications Of Mir-155 Expression In Amlmentioning
confidence: 99%